Coconut Shell Charcoal Briquettes Processing Process Using Two Modified Combustion Types - Safitriani, Dewi; Nugraha, Kris Adi; Purba, Arini Anestesia; Muttaqien, Zaenal; Fajri, Renal; Musvirah, Nur Ainun (STMIK Widya Cipta Dharma, 2024)
The process of producing briquettes from coconut shells is a promising alternative for waste utilization, creating products with high economic value for small industries. Coconut shell briquettes have a relatively high calorific value and are environmentally friendly. However, the production process, particularly in making charcoal and briquettes, still requires more efficient techniques and technology. The type of furnace used significantly affects the characteristics of the charcoal briquettes produced. The results of the study indicate that both combustion methods have a significant impact on the quality of the charcoal briquettes. The open furnace made of iron material required less time compared to the closed furnace combustion method. However, the closed furnace method is safer as it prevents direct contact with fire during combustion. In the combustion tests conducted three times using a closed furnace made of drum or zinc material, the charcoal yield was approximately 20%. A combustion test using 20 kg of coconut shell material produced 7.5 kg more charcoal with the closed furnace compared to the open furnace made of iron plate material. Additionally, the smoke produced from the closed furnace was minimal but steady throughout the combustion process. When compared to the quality requirements outlined in SNI 01-6235-2000, the results showed that five parameters met the standard requirements: moisture content, ash content, volatile matter content, fixed carbon content, and calorific value. Based on these findings, it can be concluded that both combustion methods have their respective advantages. The selection of the appropriate method can be tailored to production needs and environmental considerations.